Human intestinal spirochetosis in Japanese patients aged less than 20 years: Histological analysis of colorectal biopsy and surgical specimens obtained from 479 patients. Issue 6 (15th May 2017) - Ichimata, Shojiro; Yoshizawa, Akihiko; Kusakari, Mai; Nakayama, Yoshiko; Asaka, Shiho; Negishi, Tatsuya; Kasuga, Eriko; Matsumoto, Takehisa; Honda, Takayuki
Abstract : Human intestinal spirochetosis (HIS) is a condition in which spirochetes attach to and colonize the colorectal epithelium. To our knowledge, no comprehensive studies of HIS in young patient have been published in a developed country. This study aimed to determine the incidence and clinicopathological manifestations of HIS in Japanese patients aged less than 20 years. We retrospectively reviewed 3605 biopsy and 92 surgical specimens obtained from 479 patients admitted to Shinshu University Hospital between 1997 and 2014. All slides were reviewed independently by two pathologists to confirm the histological presence of spirochetes. Among 387 patients who underwent biopsy, the most common pathologic diagnosis was ulcerative colitis (12.6%, n = 49). Additionally, about half of the biopsy specimens showed non‐specific, mildly inflamed mucosa (50.6%, n = 196); only one of these cases was HIS. On the other hand, among the surgical specimens, we found no cases of HIS. We concluded that the incidence of HIS in Japanese young patients was 0.2% (1/479 cases). The incidence of HIS in Japanese young patients was very low, and one HIS case was associated with colitis with abdominal pain.